Quality of Anticoagulation Control in Preventing Adverse Events in Patients With Heart Failure in Sinus Rhythm. (May 2015) - Homma, Shunichi; Thompson, John L.P.; Qian, Min; Ye, Siqin; Di Tullio, Marco R.; Lip, Gregory Y.H.; Mann, Douglas L.; Sacco, Ralph L.; Levin, Bruce; Pullicino, Patrick M.; Freudenberger, Ronald S.; Teerlink, John R.; et al.
<x xml:space="preserve">Abstract</x> Background— The aim of this study is to examine the relationship between time in the therapeutic range (TTR) and clinical outcomes in heart failure patients in sinus rhythm treated with warfarin. Methods and Results— We used data from the Warfarin versus Aspirin in Reduced Cardiac Ejection Fraction (WARCEF) trial to assess the relationship of TTR with the WARCEF primary outcome (ischemic stroke, intracerebral hemorrhage, or death), with death alone, ischemic stroke alone, major hemorrhage alone, and net clinical benefit (primary outcome and major hemorrhage combined). Multivariable Cox models were used to examine how the event risk changed with TTR and to compare the high TTR, low TTR, and aspirin-treated patients, with TTR being treated as a time-dependent covariate. A total of 2217 patients were included in the analyses; among whom 1067 were randomized to warfarin and 1150 were randomized to aspirin. The median (interquartile range) follow-up duration was 3.6 (2.0–5.0) years. Mean (±SD) age was 61±11.3 years, with 80% being men. The mean (±SD) TTR was 57% (±28.5%). Increasing TTR was significantly associated with reduction in primary outcome (adjusted P<0.001), death alone (adjusted P=0.001), and improved net clinical benefit (adjusted P<0.001). A similar trend was observed for the other 2 outcomes, but significance was not reached (adjusted P=0.082 for ischemic stroke and adjusted P=0.109 for major hemorrhage). Conclusions— In patients with heart failure in sinus rhythm, increasing TTR is associated with better outcome and improved net clinical benefit. Patients in whom good quality anticoagulation can be achieved may benefit from the use of anticoagulants. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT00041938.